2001
DOI: 10.1177/030802260106400502
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapists' Views and Perceptions of Evidence-Based Practice

Abstract: In spite of the developments within health and social care, little research has been published that specifically identifies the views and perceptions that occupational therapists working in England have of evidence-based practice (EBP). This study used qualitative and quantitative methodologies in two distinct phases. Initially, focus groups were used to explore the views and perceptions that senior occupational therapists working in different settings had of EBP. In the second phase, the findings from the foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 13 publications
8
60
0
Order By: Relevance
“…OTs' and PTs' perceptions of barriers to desired use of interventions were consistent with the literature [12,48] in which participants perceived 'lack of time' as one of the main barriers. However, 'it requires special training' was of the most frequent barrier ranked as number one for OTs and PTs, again reflecting their need for more training and continuing education on specific practices for CP.…”
Section: Barriers and Enablers Of Ebpsupporting
confidence: 79%
See 3 more Smart Citations
“…OTs' and PTs' perceptions of barriers to desired use of interventions were consistent with the literature [12,48] in which participants perceived 'lack of time' as one of the main barriers. However, 'it requires special training' was of the most frequent barrier ranked as number one for OTs and PTs, again reflecting their need for more training and continuing education on specific practices for CP.…”
Section: Barriers and Enablers Of Ebpsupporting
confidence: 79%
“…However, 'it requires special training' was of the most frequent barrier ranked as number one for OTs and PTs, again reflecting their need for more training and continuing education on specific practices for CP. Surprisingly, more than one third of OTs and PTs perceived child and parent compliance as a barrier to desired use: a finding not reported previously in the literature [12,[48][49][50]. This is notable given that clinical decision-making is typically described as taking into account not only the current best evidence, but the needs of the client and family and the demands and resources of the health system [13,14].…”
Section: Barriers and Enablers Of Ebpmentioning
confidence: 99%
See 2 more Smart Citations
“…Pringle (9) (10) found that of 321 PTs surveyed in England and Australia, only 3% indicated that research articles led them to their current interventions. When 500 English OTs were asked to identify enablers of EBP, factors such as access to relevant resources, time to read and to find the evidence and to implement the evidence into practice, were identified (11). Though journals are of interest to clinicians, they do not offer a readily available consolidated source of information about specific treatment interventions.…”
Section: Introductionmentioning
confidence: 99%